Uma análise evolucionária sobre o processo de destruição criadora : a transição da indústria da música para uma economia de redes da música - Martins, Elvira Carolina Scapin (2016)
This research is an evolutionary analysis of the music industry restructuring that has been occurring since 2000. It understands that the music industry is going through a process of change and disruption in economic and institutional spheres brought about by the emergence and spread of new information and communication technologies (ICT). Digital and virtual innovations caused a "storm" of creative destruction that affected the main product that moved this industry, the disc, which is being replaced by other consumer forms of music, such as download, streaming and shows. This technological revolution originated a crisis in the music industry and its institutions and changed a business model that had existed since the 1950s. If the record companies loosed their power over the innovation process in your market and have seen their revenue decrease, on the other hand, it has seen the emergence of services network with new economic actors and new business models linked to new information and communication technologies. Thus, it is observed that the recording industry is gradually being replaced by network music services. The objective of this research is to understand the dynamics of this transition in the evolutionary perspective, in order to understand the relationship of the agents of this industry (record labels and musicians) with the new intermediates of recorded music and reflect on the main trends of the new reality of the global recorded music market